AGE AND ITS RELATION TO CRIME IN TAIWAN AND THE UNITED STATES: INVARIANT, OR DOES CULTURAL CONTEXT MATTER?*. Issue 2 (18th April 2017) - STEFFENSMEIER, DARRELL; ZHONG, HUA; LU, YUNMEI
Abstract : Current empirical and theoretical understanding of the relation between age and crime is based almost entirely on data from the United States and a few prototypical Western societies for which age‐specific crime information across offense types is available. By using Western databases, Hirschi and Gottfredson (1983) projected that the age distribution of crime is always and everywhere robustly right‐skewed (i.e., sharp adolescent peak)—a thesis that is both contested and widely accepted in criminology and social science writings. In the study described here, we tested this age–crime invariance thesis by comparing age–crime patterns in Taiwan (a non‐Western Chinese society) with those in the United States. In light of Taiwan's collectivist culture versus the U.S. individualist gestalt, we anticipated more divergence than homogeneity in their age–crime schedules. Our findings show robust divergence in Taiwan's age–crime patterns compared with U.S. patterns and the reverted J‐shaped norm projected by Hirschi and Gottfredson. Implications for research and theory on the age–crime relation and for studying human development or life‐course topics more broadly are discussed.